Rapid prototyping of an elastic bladder model for in-vitro simulation of the transurethral resection of the prostate (Transactions on Additive Manufacturing Meets Medicine, 2019)
This work presents a fabrication method for an elastic urinary bladder model with near-physiological mechanical and thermal properties using Rapid Prototyping. The model is part of an experimental setup for in-vitro simulation of the Transurethral Resection of the Prostate (TURP). Tensile tests of commercial silicone elastomers, together with FEM simulations were used to find a suitable material for the Bladder-model. A mold was then fabricated by selective laser sintering and the model was manually casted. The mechanical compliance of the finished model shows a reasonable agreement with the predicted behavior, with a max. discrepancy of 15% at 40 mbar.